2018
DOI: 10.1111/labr.12134
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Case for Intergenerational Transmission of Female Labour Force Participation and Educational Attainment? Evidence From Greece During The Crisis

Abstract: The paper investigates the intergenerational transmission of female educational attainment and the intergenerational transmission of labour force participation in Greece, in 2011. Results show that parental educational background, and especially maternal, is identified as a key determinant of women's high level of educational achievement. A wife's labour force participation decision is related to her husband's mother's and mother's participation, and even more strongly related to her own level of educational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Kawaguchi•& Miyazaki explained that sons of working women prefer working wives to traditional wives. Papapetrou & Tsalaporta (2018) suggested that in Greece, a wife's labor market participation is impacted by both her mother's and mother-in-law's participation. Li & Liu (2019) tested the correlation between daughter-in-law and mother-inlaw by son's gender-role attitude and household productivity based on Chinese data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kawaguchi•& Miyazaki explained that sons of working women prefer working wives to traditional wives. Papapetrou & Tsalaporta (2018) suggested that in Greece, a wife's labor market participation is impacted by both her mother's and mother-in-law's participation. Li & Liu (2019) tested the correlation between daughter-in-law and mother-inlaw by son's gender-role attitude and household productivity based on Chinese data.…”
Section: Literature Reviewmentioning
confidence: 99%